Assessment of noise levels of the equipments used in the dental teaching institution, Bangalore - Sushi Kadanakuppe; Padma K Bhat; C Jyothi; C Ramegowda (Wolters Kluwer Medknow Publications, 2011)
Context: In dental practical classes, the acoustic environment is characterized by high noise levels in relation to other teaching areas, due to the exaggerated noise produced by some of these devices and use of dental equipment by many users at the same time. Aims: To measure, analyze and compare noise levels of equipments among dental learning areas under different working conditions and also to measure and compare noise levels between used and brand new handpieces under different working conditions. Materials and Methods: Noise levels were measured and analyzed in different dental learning areas that included clinical, pre-clinical areas and laboratories selected as representatives of a variety of learning-teaching activities. The noise levels were determined using a precision noise level meter (CENTER® 325 IEC 651 TYPE II) with a microphone. The mean of the maxima was determined. The data were collected, tabulated, and statistically analyzed using t tests. Results: The noise levels measured varied between 64 and 97 dB(A).The differences in sound levels when the equipment was merely turned on and during cutting operations and also between used and brand new equipments were recorded. The laboratory engines had the highest noise levels, whereas the noise levels in high-speed turbine handpieces and the low-speed contra angle handpieces were decreased. Conclusion: The noise levels detected in this study are considered to be close to the limit of risk of hearing loss.